2016
DOI: 10.1186/s13195-016-0222-x
|View full text |Cite
|
Sign up to set email alerts
|

SORL1 gene, plasma biomarkers, and the risk of Alzheimer’s disease for the Han Chinese population in Taiwan

Abstract: BackgroundThe sortilin-related receptor 1 (SORL1) gene, regulating the trafficking and recycling of amyloid precursor protein, has been related to Alzheimer’s disease (AD) and mild cognitive impairment (MCI). The aim of the present study was to investigate the relationship between SORL1 polymorphisms, plasma concentrations of amyloid-beta (Aβ) isoforms, and AD and MCI susceptibility for a Han Chinese population in Taiwan.MethodsEight single-nucleotide polymorphisms (SNPs) in SORL1 and the apolipoprotein E gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
2
25
1
Order By: Relevance
“…Analysis of the results collected for MCI and AD patients did not indicate that APOE ɛ4 carriers had higher plasma NFL than non-carriers. These findings are different from previous studies which suggested MCI patients had higher plasma NFL levels than HC and APOE ɛ4 carriers had higher plasma NFL than non-carriers 1 , which may reflect the highly nuanced and complex clinical entity in MCI 23 and relatively low proportion of APOE ɛ4 carriers among the Asian AD and MCI groups 24 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…Analysis of the results collected for MCI and AD patients did not indicate that APOE ɛ4 carriers had higher plasma NFL than non-carriers. These findings are different from previous studies which suggested MCI patients had higher plasma NFL levels than HC and APOE ɛ4 carriers had higher plasma NFL than non-carriers 1 , which may reflect the highly nuanced and complex clinical entity in MCI 23 and relatively low proportion of APOE ɛ4 carriers among the Asian AD and MCI groups 24 27 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous study also reported an association between SORL1 and AD, although at the rs1784933 and rs2298813 loci. 6 Those results emphasized the roles of SORL1 also for NPS of AD. Compared with studies in other ethnic populations, the reference allele for the SORL1 rs3824968 was the A, not T, in all subpopulations of the Chinese population.…”
Section: Discussionmentioning
confidence: 86%
“…The studies we have conducted have demonstrated that the sortilin-related receptor 1 gene (SORL1) and the ATP-binding cassette, subfamily A, member 7 gene (ABCA7) are associated with AD. 5,6 Whether these high-risk genes are also involved in the presentation of NPS is not clear. For instance, the results for the apolipoprotein E (APOE) gene were inconsistent [7][8][9][10] and the evidence summarized recently in a meta-analysis revealed a negative finding.…”
mentioning
confidence: 99%
“…Additionally, Kimura et al [18], Feng et al [19], Shibata et al [20] and Wen et al [23] agreed that there is no association between rs689021 and AD. However Cousin et al [11], Ryan et al [24], Lee et al [25], Reynolds et al [26], Rowland et al [27], Lee et al [28], Cellini et al [29], and Chou et al [30] found a significant association between rs689021 and AD. It was the current authors who first analyzed the association between rs689021 and AD and reported that SNP rs689021 was associated with a decreased risk to AD among Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that SORL1 plays a significant role in AD pathogenesis [30]. The meta-analysis reported here included data from different ethnicities, thus may provide a fresh perspective into the association between SORL1 gene and AD risk.…”
Section: Discussionmentioning
confidence: 99%